Threat of Dismissal: Incentive or Sorting? - Kwon, Illoong (Journal of Labor Economics, 2005)
Many people are fired from their jobs for poor performance. However, it is difficult to distinguish whether they are fired because they are not well suited for their job (sorting explanation) or because the firms are trying to provide incentives for effort (incentive explanation). This article develops a dynamic incentive model of dismissal and proposes a methodology to distinguish between these two explanations. The methodology is based on learning‐by‐doing and changes in the slope of dismissal probability with respect to tenure. Using personnel data from a large U.S. company, this study finds significant evidence for the incentive explanation.